PSYCHOTHERAPY SUPPORT ON SCIZOPHRENIA - Suhendro, Widyawati (E-Jurnal Medika Udayana; vol 2 no 12 (2013):e-jurnal medika udayana)
Normal 0 false false false EN-US X-NONE X-NONE Schizophrenia is a disease that causes varying descriptions. The symptoms of schizophrenia are divided into two groups, the primary and secondary symptoms. Treatment should be done as soon as possible, because a state of psychotic periods raises the possibility to suffer mental decline. The treatment is carried out must be comprehensive, multimodal, empirically and can be applied to the patient. One therapy that is given is psychotherapy. Psychotherapy is usually combined with pharmacological actions in order to increase the level of maximum healing. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Scizophrenia, Psychotherapy